TERIAKKAN “PUKUL TERUS”: Misiologi Pantekosta dan Pendidikan Agama Kristen - Tambunan, Elia; Sembiring, Hesra Oktavianus; Sudjono, Andreas (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2022)
The paper presents Pantecostal missiology both historically, teaching and learning processes, as well as more recent empirical data. By not dismissing the problems and criticisms from scholars who doubted whether Pantecostalism really had a missiology, and doubted the process of learning about it in Christian religious higher education, here is narrated the dynamics of Pantecostal missiology. This paper presents the Pantecostal Church in Indonesia (PCiI or GPdI) and many things that surround it, the history of its formation since January 6, 1906 in the era of the Dutch East Indies as the object of study. To build a solid argument, based on the finding that there really is a Pantecostal missiology, we use a combined research method of quantitative empirical through a questionnaire survey for the need for a postgraduate thesis and qualitative based on primary data sources from the GPdI senior figures themselves and literature from other researchers as secondary sources. The paper is useful as a conceptual framework for the Indonesian academic field, namely Pantecostal missiology and Christian religious education which has never been the object of study so far that is useful for Christian religious higher education and global studies of Pantecostalism which is currently growing in the international academic arena. Tulisan ini menampilkan misiologi Pantekosta baik itu secara historis, proses belajar mengajar, maupun data empiris yang lebih baru. Dengan tidak menampik adanya problem dan kritik dari sarjana yang banyak meragukan apakah Pantekosta benar-benar memiliki misiologi, dan meragukan proses pembelajaran akan hal tersebut di pendidikan tinggi keagamaan Kristen, di sini dinarasikan dinamika misiologi Pantekosta. Tulisan ini mengetengahkan Gereja Pantekosta di Indonesia (GPdI) dan banyak hal yang mengitarinya sejarah pembentukannya sejak 6 Januari 1906 di era Hindia Belanda sebagai objek studi. Untuk membangun argumentasi yang solid atas dasar temuan bahwa benar ada misiologi Pantekosta, kami menggunakan metode penelitian gabungan antara kuantitatif empiris lewat survei angket untuk kebutuhan tesis pascasarjana dan kualitatif berdasarkan sumber data primer dari tokoh GPdI itu sendiri serta literatur dari peneliti lain sebagai sumber sekunder. Tulisan ini berguna menjadi kerangka konseptual dari ladang akademik Indonesia yakni misiologi Pantekosta dan pendidikan agama Kristen yang belum pernah menjadi objek kajian selama ini yang berguna bagi pendidikan tinggi keagamaan Kristen maupun studi global Pantekostalisme yang sedang menggeliat di arena akademik internasional.